ANALISIS KESALAHAN SISWA SMP PADA MATERI PERBANDINGAN DITINJAU DARI INDIKATOR KEMAMPUAN PEMECAHAN MASALAH MATEMATIS - Siti Rahmi Yuliani; Wahyu Setiawan; Heris Hendriana (Journal on Education, 2019)
This study aims to analyze student errors in working on the problem on the indicators of students' mathematical problem solving abilities in the comparison material at one of the private junior high schools in the city of Bandung. The research method is carried out quantitatively with a descriptive approach. Sampling of the research conducted was as many as 37 in one of the private junior high schools in the city of Bandung. In the technique of collecting data used tests. The test is based on indicators of mathematical problem solving abilities using five indicators with the number of questions as many as 4 items. Based on the results of tests carried out by analyzing student errors in each indicator of problem solving ability, it was found that the indicators of re-checking were the indicators with the most errors of answers.